1976
DOI: 10.1159/000231627
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Detergent on Aerosol Allergic Sensitization with Enzymes of <i>Bacillus subtilis</i>

Abstract: An anionic detergent, sodiumdodecylbenzenesulphonate, had an adjuvant effect upon aerosol allergic sensitization with subtilopeptidase A, a proteolytic enzyme of Bacillus subtilis. Both local and systemic antibody responses were accelerated and prolonged by use of the detergent. This adjuvant effect was only seen when an inactive form of the enzyme was used. The detergent, however, was able to potentiate early clinical responses upon initial exposure to the active enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…studies in mice (Kawabata et al, 1996), as No damage to the nasal tissue was seen in any of the well as from prior studies in guinea pigs (Markham and animals examined. The 0 mg Alcalase (i.e., detergent only) Wilkie, 1976Wilkie, , 1979 and monkeys (Cashner et al, 1980). It and low Alcalase dose groups showed unremarkable or very is also consistent with numerous studies in mice showing minimal submucosal infiltration of neutrophils along the adjuvant effects of different materials (e.g., diesel particles, respiratory surfaces.…”
Section: Localization Of In Administered Allergensupporting
confidence: 86%
“…studies in mice (Kawabata et al, 1996), as No damage to the nasal tissue was seen in any of the well as from prior studies in guinea pigs (Markham and animals examined. The 0 mg Alcalase (i.e., detergent only) Wilkie, 1976Wilkie, , 1979 and monkeys (Cashner et al, 1980). It and low Alcalase dose groups showed unremarkable or very is also consistent with numerous studies in mice showing minimal submucosal infiltration of neutrophils along the adjuvant effects of different materials (e.g., diesel particles, respiratory surfaces.…”
Section: Localization Of In Administered Allergensupporting
confidence: 86%
“…However, the maximum response was unchanged. The authors speculated that the LAS might have promoted penetration of the inactivated enzyme to the immune system (Markham and Wilkie, 1976). The isotype of the IgG antibodies was not reported, limiting the interpretation.…”
mentioning
confidence: 99%
“…It was postulated that other ingredients in the synthetic detergent product had adjuvant properties. Inhalation studies conducted in rhesus monkeys and guinea pigs as well as intranasal studies recently conducted in mice showed that exposure to enzyme in the presence of detergent led to a more robust immune and allergic response to the enzyme [33–36]. Additional studies in guinea‐pigs implicated the surfactants in detergent product as having the adjuvant activity (unpublished observations).…”
Section: Animal Models and Assessment Of Allergenic Potential Of Enzymesmentioning
confidence: 99%